New Challenge in International Arbitration: On-Line Hearings - Bengül KAVLAK (Revista Jurídica Portucalense, 2022)
After the outbreak of Covid-19 pandemic, to use the technological tools in judgement process has become a current issue. Particularly in arbitration, on-line hearings have come into prominence. Many of international arbitration centers issued regulations on on-line hearings since April 2020. ICC, CAS, LCIA and ISTAC may be regarded among these. Especially, ICC and ISTAC issued detailed rules on on-line hearings which include the conduct of the hearing, confidentiality of arbitration, equality of arms etc. These regulations and the attitude of international arbitration centers shows the tendency on behalf of on-line hearings during the pandemic and the post-pandemic period. When taking into consideration saving on time and cost saving qualifications of on-line hearings, it is thought that it will continue to be a good option for conducting hearings in arbitration. However, it must be kept in mind that both parties and the arbitral tribunal should exercise due diligence in conducting arbitration process to provide cyber security.